2018
DOI: 10.1080/02786826.2018.1520964
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a high-resolution supercritical differential mobility analyzer at reduced flow rates

Abstract: Classifying sub-3 nm particles effectively with relatively high penetration efficiencies and sizing resolutions is important for atmospheric new particle formation studies. A high-resolution supercritical differential mobility analyzer (half-mini DMA) was recently improved to classify aerosols at a sheath flow rate less than 100 liters per minute (lpm). In this study, we characterized the transfer functions, the penetration efficiencies, and the sizing resolution of the new half-mini DMA at the aerosol flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Aerosol standards with nanometer dimensions for instrument calibration are produced by means of electrospray generation. Previous studies (Kangasluoma et al 2013;Ude and Fern andez de la Mora 2005) have demonstrated that solutions of tetra-alkyl ammonium halides are well-suited for the clean generation of mobility standards at inverse mobilities below 2 Vs/cm 2 for instrument calibration (Cai et al 2018;Jiang et al 2011). It should be noted though that the mobility spectra for cluster ions electrosprayed from tetra-alkyl ammonium halides are dominated by larger multiply charged clusters leading to a too pronounced background to distinguish mobility peaks of singly charged clusters (Attoui et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol standards with nanometer dimensions for instrument calibration are produced by means of electrospray generation. Previous studies (Kangasluoma et al 2013;Ude and Fern andez de la Mora 2005) have demonstrated that solutions of tetra-alkyl ammonium halides are well-suited for the clean generation of mobility standards at inverse mobilities below 2 Vs/cm 2 for instrument calibration (Cai et al 2018;Jiang et al 2011). It should be noted though that the mobility spectra for cluster ions electrosprayed from tetra-alkyl ammonium halides are dominated by larger multiply charged clusters leading to a too pronounced background to distinguish mobility peaks of singly charged clusters (Attoui et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A miniature cylindrical DMA operating at a medium sheath flow rate (20-30 liters per minute) was developed to improve the penetration efficiency and size resolution for sub-3 nm particles (Cai et al 2017a). A supercritical DMA working at reduced aerosol and sheath flow rates (Cai et al 2018a; Fernández de la Mora 2017) was recently applied to improve the size resolution of a differential mobility particle spectrometer (Kangasluoma et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental setup is the classical setup and method used during the last few decades for the generation of sub-10 nm and detection-efficiency measurements with a high particle size resolution. It is widely documented in the literature [25,[42][43][44][45][46][47]. The high resolution generator is a combination of a home-made electrospray source [22] and a high resolution Attoui-type DMA [44].…”
Section: Methodsmentioning
confidence: 99%